Bacterial Cell Inactivation Using a Single-Frequency Batch-Type Ultrasound Device - Poetro Sambegoro; Maya Fitriyanti; Bentang Arief Budiman; Kamarisima Kamarisima; Sekar Wangi Arraudah Baliwangi; Calvin Alverian; Saeed Bagherzadeh; Ganesan Narsimhan; Pingkan Aditiawati; Ignatius Pulung Nurprasetio (Universitas Pendidikan Indonesia, 2021)
Ultrasound technology employs cavitation to generate high-pressure soundwaves to disrupt bacterial cells. This study reveals the effectiveness of a single frequency ultrasound device for bacterial cell inactivation. A low-cost ultrasound device having a single frequency, i.e. 22 kHz for lab-scale application, was developed first, and the prototype was mechanically designed and analyzed using the finite-element method to assure the targeted natural frequency could be achieved. The prototype was then tested inactivating bacterial cells, Escherichia coli (E. coli) and Bacillus subtilis (B. subtilis), in a simple medium and a food system, and the results were then compared to a commercial system. A treatment time of up to 15 minutes was able to reduce E. coli and B. subtilis cells by 3.3 log and 2.8 log, respectively, and these results were similar to those of the commercial system. The effectiveness of bacterial cell inactivation using the developed single-frequency ultrasound device is then discussed. The findings are useful for designing low-cost ultrasound devices for application in the food industry.